The transition to parenthood following a history of childhood maltreatment: a review of the literature on prospective and new parents’ experiences - Hope Christie; Anat Talmon; Sarah Katharina Schäfer; Anke de Haan; Maria Louison Vang; Katharina Haag; Ohad Gilbar; Eva Alisic; Erin Brown (European Journal of Psychotraumatology, 2017)
Background: Becoming a parent is viewed as one of the most important transitions in one’s life. However, a history of childhood maltreatment may affect the adjustment to parenthood. Objective: The objective of this review was to synthesize the current evidence base to further our understanding of prospective and new parents’ experiences in the transition to parenthood (pregnancy to 2 years post-birth), in the context of having a childhood maltreatment history. Method: A scoping review of the literature was conducted using the following online databases: PubMed, PsycINFO, PsycNET, and Published International Literature of Traumatic Stress. Results: The findings were synthesized into a four-component theoretical framework, which included mental health of the parent, physical changes, parental view of the child, and view of the self as a parent. A total of 69 papers, including 181,537 participants (of whom 30,482 mothers and 235 fathers had maltreatment histories), investigated the transition to parenthood. The majority of the studies showed that parents with a maltreatment history may suffer from a range of mental health problems during the transition to parenthood, experience more negative physical changes, and have more negative views of their child (or children). However, they reported both positive and negative experiences regarding their identity as a parent. Conclusions: The findings suggest that maltreatment is a risk factor for a more challenging transition to parenthood. Experiences of fathers with maltreatment histories merit more attention, as do those of parents in low- and middle-income countries. Future directions should include predictors of positive experiences and the development of early interventions to improve outcomes for this population.